New product development for new business – the critical success factor / Nordayana Zulkifli - Zulkifli, Nordayana (UiTM Cawangan Negeri Sembilan, 2022)
Developing new product is a risky and uncertain process. In order to reduce the risks and uncertainties, businesses need to evaluate their new product initiatives carefully to make accurate decisions. Although the outcome of a new product evaluation decision can be influenced by the environmental uncertainties that are beyond a company’s control, companies can successfully improve the accuracy of their new product evaluation decisions. Understanding the market and its dynamics from previous cases regarding the market, firms can make two types of erroneous decisions when evaluating their new product ideas. First, they might decide to pursue a potentially unsuccessful new product idea. Second, they might decide not to develop a potentially successful new product. In either case, firms face big losses, while the former leads to investment losses the latter leads to missed investment opportunities. It is very crucial for any business to forever believe that the marketplace is never static: it is dynamic and fast-changing, and demand for products is constantly shifting as needs, wants, and technology all change. As a result, companies must always evaluate their existing product line and look for ways to ensure that it is up to date and in line with consumer desires. Continuous decisions must be made about whether new products should be added.